73. Interim Resistance Analysis of Long-Acting Lenacapavir in Treatment-Naïve People with HIV at 28 Weeks. (4th December 2021) - VanderVeen, Laurie; Margot, Nicolas; Naik, Vidula; Chang, Silvia; Martin, Ross; Dvory-Sobol, Hadas; Rhee, Martin; Callebaut, Christian
Abstract: Background: Lenacapavir (LEN) is a first-in-class HIV-1 capsid (CA) inhibitor in clinical development for treatment and prevention of HIV-1 infection. CALIBRATE is an ongoing, phase 2 clinical study evaluating subcutaneous (SC) or oral LEN, in combination with other antiretrovirals, in treatment-naïve people with HIV-1. High rates of virologic success (HIV-1 RNA < 50 copies/mL) were achieved with LEN-based regimens by FDA Snapshot analysis at Week 28. Here, we present interim resistance analyses through Week 28. Methods: Participants were randomized (2:2:2:1) to treatment groups (TG) (Figure): SC LEN + oral daily emtricitabine/tenofovir alafenamide (F/TAF); at Week 28, participants switch F/TAF to oral TAF (TG-A) or bictegravir (B, BIC) (TG-B); oral daily LEN + F/TAF (TG-C), or oral daily B/F/TAF (TG-D). Genotypic analyses (population sequencing) of HIV-1 reverse transcriptase and integrase, and genotypic (deep sequencing)/phenotypic analyses for CA were performed at screening; genotypic and phenotypic analyses were conducted at confirmed virologic failure. Figure: CALIBRATE Study Design Results: 182 participants were randomized and dosed in TG-A to D (n=52, 53, 52, 25). Most participants had subtype B HIV-1 (92.9%). Sequence analysis of baseline samples found 65% of amino acid residues were conserved with < 1% variation across CA overall, and 55% of residues were fully conserved. No mutations were detected at 6 positions in CA associated with reduced susceptibility to LEN in vitro; residues were fully conserved at 5 positions (L56, M66, Q67, K70, N74), and < 2% variation was observed at 1 position (T107). Three participants met the criteria for resistance analysis: 2 participants resuppressed to < 50 copies/mL while continuing treatment. One participant on SC LEN + F/TAF developed emergent resistance to LEN (Q67H+K70R) and emtricitabine (M184M/I), followed by resuppression after starting dolutegravir, zidovudine + lamivudine, tenofovir disoproxil fumarate. Conclusion: Emergent resistance to LEN was uncommon in treatment-naïve participants receiving SC or oral LEN (0.6%, 1/157). These interim resistance findings support the ongoing evaluation of LEN for treatment and prevention of HIV. Disclosures: Laurie VanderVeen, PhD, Gilead Sciences (Employee, Shareholder) Nicolas Margot, MA, Gilead Sciences (Employee, Shareholder) Vidula Naik, MSc, Gilead Sciences (Employee, Shareholder) Silvia Chang, Masters, Gilead Sciences, Inc (Employee, Shareholder) Ross Martin, PhD, Gilead Sciences, Inc (Employee, Shareholder) Hadas Dvory-Sobol, PhD, Gilead Sciences (Employee, Shareholder) Martin Rhee, MD, Gilead Sciences (Employee, Shareholder) Christian Callebaut, PhD, Gilead Sciences (Employee, Shareholder)